Bulky End‐Capped [1]Benzothieno[3, 2‐b]benzothiophenes: Reaching High‐Mobility Organic Semiconductors by Fine Tuning of the Crystalline Solid‐State Order. (9th April 2015) - Schweicher, Guillaume; Lemaur, Vincent; Niebel, Claude; Ruzié, Christian; Diao, Ying; Goto, Osamu; Lee, Wen‐Ya; Kim, Yeongin; Arlin, Jean‐Baptiste; Karpinska, Jolanta; Kennedy, Alan R.; Parkin, Sean R.; et al.
Abstract : A series of bulky end‐capped [1]benzothieno[3, 2‐ b ]benzothiophenes (BTBTs) are developed in order to tune the packing structure via terminal substitution. A coupled theoretical and experimental study allows us to identify 2, 7‐di‐ tert ‐butylBTBT as a new high‐performance organic semiconductor with large and well‐balanced transfer integrals, as evidenced by quantum‐chemical calculations. Single‐crystal field‐effect transistors show a remarkable average saturation mobility of 7.1 cm 2 V −1 s −1 .